CREATING AND TACTICAL IMPLEMENTATION OF CUSTOMER SEGMENTATION FOR PRODUCTS AND SERVICES (In the Context of Uzbekistan) (International journal of artificial intelligence, 2026)
This article provides a scientific analysis of the creation of customer segmentation for products and services and its effective tactical implementation under the market conditions of Uzbekistan. The study examines the theoretical foundations of customer segmentation, including its demographic, geographic, psychographic, and behavioral types, from the perspective of the country’s socio-economic characteristics. In addition, the paper substantiates the possibilities of efficient use of marketing resources through segmentation, identification of target audiences, adaptation of products and services to local market needs, and enhancement of competitiveness. The results of the study are of practical significance for small, medium, and large business entities operating in Uzbekistan.